2021
DOI: 10.1097/j.pain.0000000000002169
|View full text |Cite|
|
Sign up to set email alerts
|

Demise of nociceptive Schwann cells causes nerve retraction and pain hyperalgesia

Abstract: The role of nociceptive Schwann cells for chronic pain is not known. We find that their demise is sufficient to cause neuropathy and neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 47 publications
3
53
0
1
Order By: Relevance
“…This irregular patterning of nociceptor terminals is also likely to change their functional connectivity with specialized cutaneous mechanosensitive glial cells at the sub-epidermal border, which are proposed to transmit nociceptive signals 49 . Consistently, ablation of these specialized Schwann cells was recently reported to cause the retraction of epidermal nerve fibres and induce allodynia 50 . Our ultrastructural morphological observations on atypical Meissner connectivity during reinnervation also raise the idea that remodelling of Meissner corpuscles anatomically links light touch to nociceptor activation in neuropathic pain, essentially ‘converting’ nociceptors to low-threshold afferents.…”
Section: Nociceptors Mediate Reinnervation Painmentioning
confidence: 55%
“…This irregular patterning of nociceptor terminals is also likely to change their functional connectivity with specialized cutaneous mechanosensitive glial cells at the sub-epidermal border, which are proposed to transmit nociceptive signals 49 . Consistently, ablation of these specialized Schwann cells was recently reported to cause the retraction of epidermal nerve fibres and induce allodynia 50 . Our ultrastructural morphological observations on atypical Meissner connectivity during reinnervation also raise the idea that remodelling of Meissner corpuscles anatomically links light touch to nociceptor activation in neuropathic pain, essentially ‘converting’ nociceptors to low-threshold afferents.…”
Section: Nociceptors Mediate Reinnervation Painmentioning
confidence: 55%
“…7,22 In recent studies, specialized nociceptive Schwann cells were characterized that form a meshlike network with nerve fibers at the dermis-epidermis border accompanying nerve fibers into the epidermis in the murine model 11 and also in human skin when assessed using electron microscopy. 12 Interestingly, selective depletion of intraepidermal nerve fibers resulted in a reduction of Schwann cell counts in murine skin, whereas ablation of Schwann cells led to nerve fiber retraction. 12 In line with these findings, we found lower numbers of Schwann cells in skin samples of SFN patients with reduced distal IENFD, but our study design did not allow conclusions about causality.…”
Section: Schwann Cell Counts Are Not Associated With Clinical Pain Ch...mentioning
confidence: 99%
“…12 Interestingly, selective depletion of intraepidermal nerve fibers resulted in a reduction of Schwann cell counts in murine skin, whereas ablation of Schwann cells led to nerve fiber retraction. 12 In line with these findings, we found lower numbers of Schwann cells in skin samples of SFN patients with reduced distal IENFD, but our study design did not allow conclusions about causality. Also, using fluorescent microscopy, we did not observe epidermal Schwann cell branches, but found them to vanish at the basement membrane.…”
Section: Schwann Cell Counts Are Not Associated With Clinical Pain Ch...mentioning
confidence: 99%
“…Consistent with this idea many studies have shown that cultured sensory neurons, whether mechanoreceptors or nociceptors, are mechanosensitive in that mechanical stimuli activate fast inward currents in these cells [7][8][9][10] . This paradigm, placing the nociceptive neuron at the center of pain control, was recently challenged by the finding that specialized nociceptive Schwann cells expressing the transcription factor Sox10 are tightly associated with sensory endings and can initiate pain 11,12 . Sox10 + Schwann cells are also found associated with mechanoreceptor endings in skin end-organs needed for touch sensation 7,13,14 .…”
mentioning
confidence: 99%